A Multidisciplinary Comparison of Different Techniques Among Skilled Water Treaders - van Duijn, Tina; Button, Chris; Masters, Rich S. W. (Frontiers in Physiology, 2021)
In an immersion incident, a person may be required to tread water for extended periods of time in order to survive. Treading water, or maintaining a stable head position above the water surface, can be achieved in several different ways. Determining which treading water techniques are economic (energetically and cognitively) is an important step in providing evidence-based water safety instruction. Skilled water treaders (n = 21) performed four common treading techniques for 3 minutes each: ‘running’ in the water, ‘flutter kick’ with hands sculling, ‘upright breaststroke’, and ‘egg-beater’. Self-reported rate of perceived exertion and task load, as well as objective measures of probe reaction time, oxygen consumption and heart rate were assessed. The ‘egg-beater’ technique and the ‘upright breaststroke’ technique were linked to significantly lower cognitive and energetic demands compared to the other techniques. Consequently, it may help to prevent drowning if inexperienced treaders learn either of these techniques early in their aquatic skills development.